RELACIÓN DE LA FUERZA EN CUÁDRICEPS , LA FUNCIÓN Y LA SINTOMAS DE LA RODILLA ENTENDINOPATÍA ROTULIANA EN PERSONAS QUE ENTRENAN FUERZA - Cusme Castro, Cristian Xavier (2025)
The purpose of this research was to analyze the relationship between quadriceps strength, function, and symptomatology of patellar tendinopathy in individuals who train in a gym setting. A quantitative, observational, prospective, and cross-sectional study was conducted with a sample of 92 participants (aged 18 to 35), all of whom had at least six months of strength training experience. Anthropometric variables were assessed, quadriceps strength was measured using a portable dynamometer (Kinvent), and function/pain was evaluated through the VISA-P questionnaire. The results showed that quadriceps strength had a very weak correlation with pain associated with patellar tendinopathy (r = 0.0878 in participants with tendinopathy and r = -0.0026 in those without tendinopathy). These findings indicate that although muscle strength is important for knee stability, it is not a primary predictor of pain in this condition. In conclusion, patellar tendinopathy is a multifactorial phenomenon influenced not only by muscle strength but also by biomechanical, functional, and load-related factors. Therefore, quadriceps strengthening alone may not be sufficient for symptom reduction, highlighting the need for a comprehensive approach to prevention, treatment, and rehabilitation.